2000
DOI: 10.1086/314317
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Calibration: What Consumers Know and What They Think They Know

Abstract: Consumer knowledge is seldom complete or errorless. Therefore, the self-assessed validity of knowledge and consequent knowledge calibration (i.e., the correspondence between self-assessed and actual validity) is an important issue for the study of consumer decision making. In this article we describe methods and models used in calibration research. We then review a wide variety of empirical results indicating that high levels of calibration are achieved rarely, moderate levels that include some degree of syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
556
5
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 651 publications
(604 citation statements)
references
References 261 publications
(291 reference statements)
32
556
5
11
Order By: Relevance
“…Research on overconfidence has found that subjective and objective measures of performance are poorly correlated (see Alba & Hutchinson, 2000 for a comprehensive review).…”
Section: How Perceptions Of Difficulty Drive Miscalibration In Relatimentioning
confidence: 99%
“…Research on overconfidence has found that subjective and objective measures of performance are poorly correlated (see Alba & Hutchinson, 2000 for a comprehensive review).…”
Section: How Perceptions Of Difficulty Drive Miscalibration In Relatimentioning
confidence: 99%
“…The overconfidence effect is prominent among the cognitive illusions catalogued by the heuristics-and-biases program, and it has received considerable research attention (for reviews, see Alba & Hutchinson, 2000;Hoffrage, in press;Lichtenstein, Fischhoff, & Phillips, 1982). Overconfidence research is essentially concerned with achievement, measured in terms of the extent to which people are calibrated to the accuracy of their knowledge.…”
Section: Does "Overconfidence" Disappear In Representative Designs?mentioning
confidence: 99%
“…doi:10. /j.appet.2007 preferences in domains not related to food is often relatively low (Alba & Hutchinson, 2000). Hoch (1987) asked participants to predict the attitudes, interests, and purchase behaviors of their spouses, their peers (married MBA students), and the average American consumer.…”
Section: Prediction Accuracymentioning
confidence: 99%